Morphological variation across space does not predict phenotypic change through time in two Neogene planktonic foraminifera species - Brombacher, Anieke; Wilson, Paul A.; Bailey, Ian; Ezard, Thomas H. G. (Frontiers in Ecology and Evolution, 2023)
Lines of least resistance, or the direction of maximum phenotypic variation, are reliable predictive tools for directions of evolutionary divergence through time. However, the consistency of trait covariation patterns through space, i.e. in different populations of the same taxa inhabiting different environmental settings, remains poorly established. To test whether the predicted direction of evolutionary change is the same through time as it is across space, we compare within- and among-population trait covariation patterns across six Atlantic populations of two planktonic foraminifera species. Our study interval is 600,000 years long, spans the Neogene/Quaternary boundary and includes Earth’s most recent major natural shift in global climate state: the intensification of Northern Hemisphere Glaciation. We show that, despite these powerful global temporal changes in climate, there is a strong spatial signal in the evolutionary response. Population-specific trait covariation slopes vary among sites, climate phases and core/edge position within the species’ biogeographic range, implying that the direction of expected evolutionary change does not align across populations. Our results suggest that trait covariation patterns in the study species are driven by adaptation to local environmental settings rather than species-wide constraints. Single populations should therefore not be used to predict the response of other populations, even if they are faced with similar environmental conditions. We caution against using individual populations to project future response of other/global populations unless the underlying mechanism for trait covariation is shown to be universal.